Palliative resection or radiation of primary tumor prolonged survival for metastatic esophageal cancer. (14th October 2019) - Xu, Jing; Lu, Donghui; Zhang, Li; Li, Jian; Sun, Guoping
Abstract: Purpose: We aimed to explore the value of palliative resection or radiation of primary tumor for metastatic esophageal cancer (EC) patients. Methods: Surveillance, Epidemiology, and End Results database was used for identifying metastatic EC patients. The patients were divided into resection and nonresection groups. And patients without resection were divided into radiation and nonradiation groups. Propensity score matching (PSM) analyses were adopted to reduce the baseline differences between the groups. Cancer specific survivals (CSSs) and overall survivals (OSs) were compared by Kaplan‐Meier (K‐M) curves. Multivariable analyses by COX proportion hazards model were performed to identify risk factors for CSS and OS. Predictive nomograms were conducted according to both postoperative factors and preoperative factors. Results: A total of 7982 metastatic EC patients were selected for our analyses. After PSM, 978 patients were included in the survival analyses comparing palliative resection and nonresection. The CSS and OS for patients underwent palliative resection were significantly longer than those without resection (median CSS: 21 months vs 7 months, P  < .001; median OS: 20 months vs 7 months, P  < .001). In the overall population without resection, 654 patients were matched for radiation and nonradiation groups. And K‐M curves showed that patients with radiation had longer CSS and OS than those without radiation (median CSS: 11 months vs 6 months, P  < .001; median OS: 10 months vs 6 months, P  < .001). Nomograms were generated for prediction of 1‐, 2‐, and 3‐year CSS and OS. All C‐indexes implied moderate discrimination and accuracy. And all nomograms had good calibration. Conclusion: Palliative resection or radiation of primary tumor could prolong CSS and OS of metastatic EC patients. Abstract : This study aimed to evaluate the value of palliative resection or radiation of primary tumor for metastatic esophageal cancer using the Surveillance, Epidemiology, and End Results database. Additionally, we constructed prognostic nomograms for both preoperative and postoperative risk factors. We found that palliative resection or radiation could improve the survival of such patients, across both squamous cell carcinoma and adenocarcinoma.